A NOVEL APPLICATION OF HYDROTROPIC SOLUBILIZATION IN DEVELOPMENT AND VALIDATION OF SPECTROPHOTOMETRIC METHOD FOR SIMULTANEOUS ESTIMATION OF PARACETAMOL AND DICLOFENAC SODIUM IN SOLID DOSAGE FORM - RAJESH SHARMA,; GEETAM PATHODIYA,; GANESH PRASAD MISHRA, (International Journal of Pharma and Bio Sciences, 2010)
Three simple, rapid, accurate and economical analytical methods are described for the determination of Paracetamol and Diclofenac sodium in combined tablet dosage form. In the present investigation, 1.0 M urea solution (hydrotropic solubilizing agent) was employed to solubilize, Paracetamol (a poorly watersoluble drug) from fine powder of its tablets to carryout spectrophotometric analysis. Simultaneous estimation was carried out by three method, Method –A derivative spectrophotometry method, MethodB area under curve method and Method-C multi-component method.The result showed that Beer’s law was obeyed in concentration range of 2-40 µg/ml with good linearity (r2>0.99) for both the drugs in all the three methods. The recoveries were within 98.93-101.01% for paracetamol and 99.6-101.4% for diclofenac sodium. Precision was good with acceptable limits of detection (LOD) and quantitation (LOQ) for both compounds. The average content of the compounds were 100.22 and 99.11% in method-A, 99.05 and 101.32% in method-B and 99.98 and 100.90% in method-C for paracetamol and diclofenac sodium respectively. The optimized methods showed good reproducibility and recovery with standard deviation of < 1.0% and percent relative standard deviation less then 2.0%.